UJI EFEKTIVITAS LARVASIDA EKSTRAK DAUN JAMBU METE (Anacardium occidentale Linn) TERHADAP LARVA Aedes aegypti - Shofwan Haris, M.; Norhalisah, Norhalisah (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2023)
One way to control this mosquito vectois by using larvicides derived from cashew leaves. Cashew leaf extract (Anacardium occidentale Linn) is thought to have an effect as a larvicide against Aedes aegpti because it has various active metabolite substances in the form of flavonoids, alkaloids, and tannins that can inhibit the development and growth of Aedes aegpti larvae. The purpose of this study is to determine the larvicidal effectiveness of cashew leaf extract (Anacardium occidentale Linn) against Aedes aegpti larvae. This research design used experimental with the research subjects as many as 30 Aedes agypti IsntaIII larvae. The research subjects were divided into 4 treatment groups. The concentrations used in this study were 8%, 9%, 10% negative control (Aquades), positive control (Abate). Observations were made at 6 hours, 12 hours, 18 hours, and 24 hours aftetreatment with replication foutimes. Data were analyzed by Kolgomorov-Sminorv test and continued with Kruskal-Wallis test and then calculation of Lethal concentration value using probit analysis. Probit analysis results LC50 value was at a concentration of 9.242% and LC90 value was at a concentration of 9.504%. Cashew leaf extract (Anacardium occidentale Linn) had a larvicidal effect against Aedes aegpti larvae at LC50 with a concentration of 9.242%. The Conclusion cashew leaf extract (Anacardium occidentale Linn) at a concentration of 9.242% was able to kill 50% of Aedes aegpti larvae exposed fo24 hours. Future researchers are expected to improve the provision of extracts by combining them with othetypes of extracts.